ANALISIS PENGARUH PROFITABILITY DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DEVIDEN DENGAN LIKUIDITAS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2015 – 2019) - Susanto, Defri; Pancawardani, Nurul Latifah; Mohklas, Mohklas (STIE PENA, 2022)
ABSTRACT This study aims to analyze the effect of profitability and investment opportunity set on dividend policy with liquidity as a moderating variable. The independent variables used in this study are profitability and investment opportunity set. The moderating variable in this study is liquidity. The dependent variable in this study is dividend policy. This study uses secondary data derived from the annual financial statements. The population in this study are banking companies listed on the Indonesia Stock Exchange for the period 2015 - 2019. The sampling technique used is purposive sampling and the number of samples is 55 data. The data analysis method used Interaction Test or Moderate Regression Analysis (MRA). The results of this study indicate that profitability has no effect on dividend policy. The investment opportunity set has no effect on dividend policy. Liquidity does not moderate the effect of profitability on dividend policy. Liquidity does not moderate the effect of the investment opportunity set on dividend policy.Keyword : Profitability, Investment Opportunity Set, Likuidity, Dividend Policy.